(untitled) (Sains Humanika, 2012)
This survey is conducted to identify the teaching styles of 32 social science lecturers from Faculty of Management and Human Resource Development, Universiti Teknologi Malaysia (UTM) who are teaching adult learners at the School of Professional Continuing Education (SPACE), UTM. In this study the teaching styles refer to teacher-centered and learner-centered styles which were introduced by Conti (1989). The teaching styles would be assessed using the Principles of Adult Learning Scale questionnaire (PALS) which evaluate 7 factors such as learner - centered activities, personalizing instruction, relating to experience, assessing students needs, climate building, participation in the learning process and flexibility for personal development. This study found that majority of the lecturers involved used a combination of teacher-centered and learner-centered styles in teaching adult learners.